Visual wayfinding for partially sighted pedestrians – The use of luminance contrast in outdoor pavings. (October 2019) - Laurìa, A; Secchi, S; Vessella, L
An increase in the number of partially sighted people is one of the effects of population ageing. These people have great difficulties in gathering wayfinding information to move independently in an unfamiliar environment. Guide paths based on the luminance contrast between a strip and surrounding surfaces can be an effective device for mitigating these difficulties, but information provided by the scientific literature on guide paths cannot be usefully applied to the naturally coloured paving materials most commonly found in pedestrian urban spaces. This paper presents a simplified method for measuring the luminance contrast between a guide strip and its background using combinations of naturally coloured paving materials.